Decline of Humoral Responses against SARS-CoV-2 Spike in Convalescent Individuals - Guillaume Beaudoin-Bussières (American Society for Microbiology, 2020)
ABSTRACT In the absence of effective vaccines and with limited therapeutic options, convalescent plasma is being collected across the globe for potential transfusion to coronavirus disease 2019 (COVID-19) patients. The therapy has been deemed safe, and several clinical trials assessing its efficacy are ongoing. While it remains to be formally proven, the presence of neutralizing antibodies is thought to play a positive role in the efficacy of this treatment. Indeed, neutralizing titers of ≥1:160 have been recommended in some convalescent plasma trials for inclusion. Here, we performed repeated analyses at 1-month intervals on 31 convalescent individuals to evaluate how the humoral responses against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Spike glycoprotein, including neutralization, evolve over time. We observed that the levels of receptor-binding-domain (RBD)-specific IgG and IgA slightly decreased between 6 and 10 weeks after the onset of symptoms but that RBD-specific IgM levels decreased much more abruptly. Similarly, we observed a significant decrease in the capacity of convalescent plasma to neutralize pseudoparticles bearing wild-type SARS-CoV-2 S or its D614G variant. If neutralization activity proves to be an important factor in the clinical efficacy of convalescent plasma transfer, our results suggest that plasma from convalescent donors should be recovered rapidly after resolution of symptoms. IMPORTANCE While waiting for an efficient vaccine to protect against SARS-CoV-2 infection, alternative approaches to treat or prevent acute COVID-19 are urgently needed. Transfusion of convalescent plasma to treat COVID-19 patients is currently being explored; neutralizing activity in convalescent plasma is thought to play a central role in the efficacy of this treatment. Here, we observed that plasma neutralization activity decreased a few weeks after the onset of the symptoms. If neutralizing activity is required for the efficacy of convalescent plasma transfer, our results suggest that convalescent plasma should be recovered rapidly after the donor recovers from active infection.